PPG Peptide Nucleic Acids that Promote DNA Guanine Quadruplexes. Issue 13 (8th July 2014) - Englund, Ethan A.; Gupta, Pankaj; Micklitsch, Christopher M.; Onyshchenko, Mykola I.; Remeeva, Evgenia; Neumann, Ronald D.; Panyutin, Igor G.; Appella, Daniel H.
Abstract Recent studies have shown that guanine‐rich (G‐rich) sequences with the potential to form quadruplexes might play a role in normal transcription as well as overexpression of oncogenes. Chemical tools that allow examination of the specific roles of G‐quadruplex formation in vivo, and their association with gene regulation will be essential to understanding the functions of these quadruplexes and might lead to beneficial therapies. Properly designed peptide nucleic acids (PNAs) can invade G‐rich DNA duplexes and induce the formation of a G‐quadruplex in the free DNA strand. Replacing guanines in the PNA sequence with pyrazolo[3, 4‐d]pyrimidine guanine (PPG) nucleobases eliminates G‐quadruplex formation with PNA and promotes invasion of the target DNA.